Myeloperoxidase Content is a Marker of Systemic Inflammation in a Chronic Condition: The Example Given by the Periodontal Disease in Rats. (31st December 2009) - Queiroz-Junior, Celso Martins; Pacheco, Cinthia Mara da Fonseca; Fonseca, Allyson Henrique; Klein, André; Caliari, Marcelo Vidigal; de Francischi, Janetti Nogueira
Abstract : The study aimed to evaluate the suitability of myeloperoxidase (MPO) content as a local indicator of chronic inflammation, using the periodontal disease model. Anesthetized adult male Holtzman rats had their second left maxilar molar tied by a thread for 11 days and were then killed. Blood samples and photographic images from histopathological inflamed and noninflamed (contralateral) neighboring gingivomucosal specimens were collected for cell counts and MPO level analysis. Diseased animals were also treated with pharmacological tools such as the anti-inflammatory drug celecoxib or the opioid morphine. Increased blood neutrophils and local cell numbers characterized diseased animals. However, local MPO content was increased in inflamed and noninflamed tissues from diseased animals. Celecoxib and morphine reduced blood neutrophils and bilateral MPO content, but only celecoxib reduced local cell numbers in diseased animals. It is concluded that MPO content is a good indicator of a systemic rather than a local inflammation in a chronic inflammatory condition.